Carissa carandas: A multi-faceted approach to health, wellness, and commerce - Wisha Saeed; Tariq Ismail; Muhammad Qamar; Muhammad Zulqarnain Khan; Naveed Ahmad; Mohammad S. Mubarak; Tuba Esatbeyoglu (Journal of Agriculture and Food Research)
Carissa carandas (C. carandas), an Apocynaceae family member, fruit bearing crop is locally known as karonda in Asia, grown wild has gained attention owing to impressive nutritional composition and health benefits. A 100–200 g serving size of C. carandas meets 100 % recommended dietary allowance (RDA) of iron, zinc, manganese, copper, chromium, and vitamin C in all age groups, making it a promising candidate for addressing nutrient deficiencies across all age groups. Other than that it also contains significant amount of carbohydrates (61–67 %) sugars (4.7–13 % mainly reducing), fats (4.5–19 % mainly PUFAS), and protein (1.6–3.2 %) despite remaining underutilized. C. carandas extracts reported to have antioxidant, anti-inflammatory, antimicrobial, and anti-tyrosinase potential comparable to the commercially available synthetic drugs. Therefore, this review aims to consolidate current knowledge on the nutritional profile and bioactive components of C. carandas, and to explore its importance in food technology sector. The study provides novel insights about the potential of C. carandas to address micronutrient deficiencies, boost local economies, and provide income for farmers. It also highlights its potential for sustainable agriculture, functional food development, and innovative products due to its antioxidant, antimicrobial, and anti-inflammatory properties.